Extensor Carpi Radialis Longus Tenodesis Using a Biotenodesis Screw for Treatment of Symptomatic Geissler 2 Scapholunate Dissociation - Stone, Andrew; Shahid, Zuhaib; Agarwal, Sujit; Sarkhel, Tanaya (Journal of Hand and Microsurgery, 2019)
Treatment of scapholunate dissociation (SLD) depends on the degree of injury. We present our technique of extensor carpi radialis longus (ECRL) tenodesis for Geissler grade 2 SLD and our preliminary results. After arthroscopic confirmation of Geissler grade 2 SLD, we use a single incision and a polyetheretherketone (PEEK) anchor, attaching half of the ECRL tendon to the scaphoid. Preliminary results include improvements in QDASH, QDASH (work) and QDASH (sports/music), a median satisfaction level of 4/5 (satisfied), and a low complication rate. Our method is a safe, reproducible, and effective treatment of symptomatic Geissler grade 2 SLD that has failed nonoperative management, with technical advantages over alternative methods in the literature.
Keywords: scapholunate; extensor carpi radialis longus; tenodesis; biotenodesis; Geissler grade 2